2019
DOI: 10.1029/2018jd030157
|View full text |Cite
|
Sign up to set email alerts
|

SuperDARN Observations of Semidiurnal Tidal Variability in the MLT and the Response to Sudden Stratospheric Warming Events

Abstract: Using meteor wind data from the Super Dual Auroral Radar Network (SuperDARN) in the Northern Hemisphere, we (1) demonstrate that the migrating (Sun‐synchronous) tides can be separated from the nonmigrating components in the mesosphere and lower thermosphere (MLT) region and (2) use this to determine the response of the different components of the semidiurnal tide (SDT) to sudden stratospheric warming (SSW) conditions. The radars span a limited range of latitudes around 60°N and are located over nearly 180° of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 51 publications
9
40
0
Order By: Relevance
“…This minimum was also reported in a case study on SSW 2009 at high latitude and a multiyear statistical study at midlatitude (He et al, ; He & Chau, ), which was attributed to energy exports in nonlinear interactions with planetary waves through the mechanism of planetary wave amplification by stimulated tidal decay. While our S2 weakening result is consistent with some abovementioned observational studies (He et al, ; He & Chau, ; Hibbins et al, ), it looks contrary to some reports of S2 enhancements during SSWs (e.g., Sridharan et al, ). The contradiction is potentially due to the fact that the enhancement and weakening are referring to different SSW stages, and time scales.…”
Section: Discussionsupporting
confidence: 85%
“…This minimum was also reported in a case study on SSW 2009 at high latitude and a multiyear statistical study at midlatitude (He et al, ; He & Chau, ), which was attributed to energy exports in nonlinear interactions with planetary waves through the mechanism of planetary wave amplification by stimulated tidal decay. While our S2 weakening result is consistent with some abovementioned observational studies (He et al, ; He & Chau, ; Hibbins et al, ), it looks contrary to some reports of S2 enhancements during SSWs (e.g., Sridharan et al, ). The contradiction is potentially due to the fact that the enhancement and weakening are referring to different SSW stages, and time scales.…”
Section: Discussionsupporting
confidence: 85%
“…Hence, our results complement and extend the observational study of Hibbins et al. (2019) using SuperDARN and the model study of Limpasuvan et al. (2016) based on WACCM as well as the work of He and Chau (2019) using SMR.…”
Section: Introductionsupporting
confidence: 88%
“…Recently, Hibbins et al. (2019) combined multiple, simultaneous single‐station radar observations to separate longitudinal from temporal variations and to explicitly extract SW1, SW2, and SW3. Clustered around 60°N, these stations measure horizontal winds around 95 km as part of the Super Dual Auroral Radar Network (SuperDARN).…”
Section: Introductionmentioning
confidence: 99%
“…For comparison with ground-based instruments, vertical profiles of NAVGEM-HA analyzed winds and temperatures are converted from the model vertical grid in geopotential altitude to a geometric altitude grid. To date, NAVGEM-HA winds and tides have been shown to be in good agreement with ground-based meteor radar observations (McCormack et al, 2017;Eckermann et al, 2018;Laskar et al, 2019;Stober et al, 2020) and with independent satellite-based wind observations as reported in Dhadly et al (2018). In the present study we employ NAVGEM-HA analyzed winds at 82.5 km altitude, staying below altitudes where effects of increased numerical diffusion imposed at the NAVGEM-HA upper boundary may impact the tides, to validate the method of extracting migrating tidal signatures from the SD meteor wind data.…”
Section: Navgem-hasupporting
confidence: 62%